(untitled) (Journal of Global Humanities and Social Sciences, 2025)
In this paper,9 Chinese characters related to fertility culture are listed and analyzed from three aspects: gestate of life, birth of life and upbringing of life. Combined with the research of ancient and modern Chinese and western medicine, the definition of Chinese characters composition and evolution is further enriched.